Climate distress and social identity: bringing theory to clinical practice - Williams, Marc O. (Frontiers in Psychology, 2023)
Guidance for supporting individuals with climate distress often lacks a theoretical foundation to account for its social dimension. This paper argues for the value of the social identity approach (SIA) for understanding and supporting individuals with climate distress in clinic. Three aspects of climate distress are considered: social isolation, collective emotions, and climate action. It is posited that the SIA can guide interventions in a way that is tailored to the specific social dynamics entailed in each client's climate distress. The paper also considers how clinicians can weigh up the potential advantages and disadvantages of interventions that are commonly advised for these individuals, such as contact with nature and engaging in collective action. The author is a clinical psychologist and lecturer researching climate distress.